2016
DOI: 10.1002/cpp.2048
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Changes Predict a Decrease in Symptoms in CBT for Depression: An Exploratory Study

Abstract: Elaborating innovative moments (IMs) that are new ways of thinking, feeling, behaving and relating, in the therapeutic dialogue, may facilitate change. IMs that are more predictive of amelioration of symptoms in CBT are the ones focused on contrasts between former problematic patterns and new adjusted ones; and the ones in which the clients elaborate on processes of change. Therapists may integrate these kinds of questions (centred on contrasts and centred on what allowed change from the client's perspective),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 35 publications
(105 reference statements)
4
42
0
Order By: Relevance
“…This study consists of a reanalysis of a sample of MDD (Gonçalves et al, , N = 10; Gonçalves, Silva, et al, , N = 6). This sample comprises 16 participants diagnosed with MDD from a controlled clinical trial conducted in a university clinic at Braga, Portugal, comparing the effectiveness of NT and CBT (Lopes et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study consists of a reanalysis of a sample of MDD (Gonçalves et al, , N = 10; Gonçalves, Silva, et al, , N = 6). This sample comprises 16 participants diagnosed with MDD from a controlled clinical trial conducted in a university clinic at Braga, Portugal, comparing the effectiveness of NT and CBT (Lopes et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Reliability has proved to be strong at both recognizing IM proportion, ranging from 84% to 94%, and identifying IM types with Cohen's κ ranging from 0.80 to 0.97 (for a complete review of previous studies, see Gonçalves, Ribeiro, et al, ). IMs were already coded in previous studies, including reconceptualization (Gonçalves et al, for NT; Gonçalves, Silva, et al, for CBT). For the purposes of this study, only reconceptualization IMs will be considered.…”
Section: Methodsmentioning
confidence: 99%
“…The Innovative Moments Coding System (IMCS) (Gonçalves, Ribeiro, et al, ; Gonçalves, Ribeiro, Mendes, Matos, & Santos, ; Gonçalves, Silva, et al, ), despite departing from a narrative tradition in psychotherapy (White & Epston, ), proposes a systematic way of tracking the transformation of clients' MFM through the identification of innovative moments (IMs). As this transformation occurs, the MFM is challenged and revised, and an alternative framework of meaning (AFM) emerges.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a bottom‐up strategy, the empirical research suggested that IMs may emerge into seven different types, which can be further organised into two or three levels (Table ). In this article, we focus on the organisation of the IMs into three levels (Fernández‐Navarro, Ribeiro, Soylemez, & Gonçalves, ; for information on the IMs types, see Gonçalves, Ribeiro, et al, ; Gonçalves, Silva, et al, ). This organisation reflects the empirical results with the IMCS and presents a hierarchical structure, from level 1 IMs representing initial steps in constructing change to level 3 IMs reflecting a more consolidated change.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IMs are new ways of acting, feeling, and thinking-ways that are alternative to the problematic pattern of meaning. This method of analysis of psychotherapy change has been applied to a wide diversity of problems (e.g., depression, prolonged grief, wife abuse) and therapeutic models, such as narrative therapy (Matos, Santos, Gonçalves, & Martins, 2009;Gonçalves, Ribeiro, Silva, Mendes, & Sousa, 2016), emotion-focused therapy (Mendes et al, 2010), clientcentered therapy , constructivist therapy (Alves et al, 2014), and cognitive-behavior therapy (Gonçalves et al, 2015). From these studies, several systematic findings emerged: (1) IMs occur more in recovered than in unchanged cases; (2) IMs emerge in five different types-three elementary types (action, reflection, protest) and two complex types (reconceptualization and performing change) (see Table 2 .…”
mentioning
confidence: 99%